2018
DOI: 10.1071/mf17357
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination of tangled lignum (Duma florulenta) and nitre goosefoot (Chenopodium nitrariaceum) under experimental hydrological regimes

Abstract: The distribution of plants on flood plains depends on the hydrological regime on the flood plain and the hydrological requirements of the plants. The aims of the present study were to: (1) determine the relationships between germination of tangled lignum (Duma florulenta) and nitre goosefoot (Chenopodium nitrariaceum) and hydrological regime; (2) determine the buoyancy of the seeds of the two species, and hence the ability of the seeds to disperse by water; and (3) inform environmental flow requirements for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Despite this, patterns of pairwise genetic differentiation and clustering according to STRUCTURE suggest a pattern of genetic variation best explained by floodplain dispersal via hydrochory. This is in agreement with experimental data finding that lignum seeds can germinate while floating and achieve optimal germination when inundation occurs for around 20 days before seeds are deposited on to wet soil (Chong & Walker, ; Higgisson et al, ). Despite the apparent importance of dispersal via floodwater, flow variables did not significantly explain genetic variation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Despite this, patterns of pairwise genetic differentiation and clustering according to STRUCTURE suggest a pattern of genetic variation best explained by floodplain dispersal via hydrochory. This is in agreement with experimental data finding that lignum seeds can germinate while floating and achieve optimal germination when inundation occurs for around 20 days before seeds are deposited on to wet soil (Chong & Walker, ; Higgisson et al, ). Despite the apparent importance of dispersal via floodwater, flow variables did not significantly explain genetic variation.…”
Section: Discussionsupporting
confidence: 92%
“…This process is rapid and the time from anthesis to the production of viable seed can be as little as 14 days (Chong & Walker, ). Seeds remain buoyant for up to 49 days and germinate readily given moisture and fluctuating temperatures (Chong & Walker, ; Higgisson, Briggs, & Dyer, ). A lack of viable seeds in soil samples and the absence of lignum seedlings in soil germination experiments (Capon & Reid, ; Dawson et al, ; Reid, Reid, & Thoms, ) indicate that seeds do not remain viable for long periods either on the plant or in the soil, suggesting the species is not reliant on a dormant soil seed bank (Chong & Walker, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental flows have been used for many years to improve riverine health with various outcomes, including triggering fish spawning and recruitment events, assisting waterbird breeding, and maintaining the geomorphological structure and habitat of rivers (Amtstaetter, O'Connor, & Pickworth, ; King et al, ; Thoms & Sheldon, ; Whiting, ). However, in recent years, there has been greater interest in the effect of natural or environmental flows at stimulating seedling emergence from seed banks in riparian systems and the characteristics of flow that relate to germination, including inundation duration (e.g., Webb et al, ; Higgisson et al, ), flood gradient, or landscape position (Dawson et al, ), water level fluctuations (e.g., Sarneel, Janssen, Rip, Bender, & Bakker, ), and flood frequency (e.g., Casanova & Brock, ). Higgisson et al () examined the germination response of two plant species from seedbank material subjected to different periods of inundation, concluding that environmental flows need to consider the germination requirements of these species.…”
Section: Discussionmentioning
confidence: 99%
“…However Harris, Leishman, and Fryirs (), using a limited number of species, found that inundation depth (at 5, 75, and 180 cm) is not a key factor in germination from the seed bank of the desirable riparian species from our case study region, the Hunter Valley. Although other studies have examined the effects of inundation duration on species germination (e.g., Webb, Reid, Capon, Thoms, & Rayburg ; Higgisson, Briggs, & Dyer, ; Capon et al, ), the effects of flow duration on the suite of desirable Hunter Valley species have not been tested.…”
Section: Introductionmentioning
confidence: 99%